2004
DOI: 10.1159/000076245
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal Hyperplasia after Stenting in a Human Mammary Artery Organ Culture

Abstract: Although the use of stents has limited the incidence of restenosis, in-stent restenosis remains an important problem. In-stent restenosis is the result of a healing process that induced neointimal hyperplasia through mechanisms that are still not understood. The aim of this study was to analyze the histological consequences of the healing process following stent implantation. Internal mammary arteries from atheroslerotic patients undergoing coronary artery bypass surgery were stented and maintained in culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…However, quantitatively, there is no perfect correlation between RhoA activity, p27 levels and the mitotic activity in the arterial wall [20]. This observation suggests that other regulators of the cell cycle might participate in the control of cell proliferation involved in the neointima formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, quantitatively, there is no perfect correlation between RhoA activity, p27 levels and the mitotic activity in the arterial wall [20]. This observation suggests that other regulators of the cell cycle might participate in the control of cell proliferation involved in the neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…Stenting and organ culture were performed as previously described [20]. Briefly, unused segments of internal mammary arteries (2–3 cm long) were obtained from patients undergoing coronary bypass surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial segments measuring approximately 2 cm were subjected to balloon dilatation (3ϫ30 s, 10 ATM) followed by stent implantation by 30 s inflation at 10 ATM, as previously described. 17 The stented arterial samples were subsequently cultured in serum-containing medium for 14 days at 37°C in 95% air/5% CO 2 in the absence or presence of LTB 4 (100 nmol/L), with change of medium every 2 days. Morphological analysis of intimal hyperplasia was performed as described above.…”
Section: Human Artery Organ Culturementioning
confidence: 99%
“…11 In the case of DES implantation after predilatation, it was shown that if the DES did not cover the entire predilated segment, the edge area free of endothelial cells would be at risk of an edge effect caused by a increased neointimal thickness. 12 Lemos et al 13 confirmed that edge restenosis was associated with balloon trauma outside the stented segment.…”
Section: Discussionmentioning
confidence: 99%